Magnetic and magneto caloric properties of melt-spun rare earth intermetallic compound DyAl2. Issue 1 (1st March 2022) - Prusty, Mitali Madhusmita; Arout Chelvane, J.; Morozkin, A. V.; Nirmala, R.
Abstract: Laves phase rare earth intermetallic compound DyAl2 has been prepared by melt-spinning under argon atmosphere. The melt-spun DyAl2 sample is crystalline (cubic structure, space group Fd-3m) and is nanostructured. The crystallite size of melt-spun DyAl2 calculated from the room temperature powder X-ray diffraction data is about 23 nm. Transmission electron microscopy image reveals particles of average size, 14 nm. The melt-spun DyAl2 undergoes a paramagnetic to ferromagnetic transition at ∼29 K (TC ). This value is about 32 K lower than the ferromagnetic transition temperature of DyAl2 sample prepared by conventional arc-melting technique. Magnetization of the melt-spun DyAl2 does not saturate at 2 K in field of 70 kOe. Magnetic entropy change near TC has been calculated using the field dependent magnetization data. The maximum value of isothermal magnetic entropy change (ΔSm ) of melt-spun DyAl2 is ∼ -10.5 Jkg −1 K- 1 at 30 K for a field change of 70 kOe. The ΔSm value is as large as -24 Jkg −1 K- 1 at 63 K for the arc-melted DyAl2 compound for the same field change. The formation of nanograins upon melt-spinning has led to the reduction of TC as well as the magnetocaloric effect around TC .